Gazdaság és regionalitás: Horvátország - Lőrinczné Bencze, Edit (Közép-Európai Közlemények, 2012)
The aim of the paper is to analyse characteristics features of regional and economic disparities of former Yugoslavia as well as Croatia. The study introduces the three broad geographical regions –Pannonian, Mediterranean and Mountainous –and their economic differences, the economic nationalism emerging in two Yugoslavias. To demonstrate the various stepping-stones of this tendency the major differences among regions are shown and three indicators of economic development are ex-amined. It is proved that Slovenia and Croatia and portions of Serbia –so called North –are ad-vanced, but the rest of the country –South –is essentially underdeveloped. The economic development in Croatia is heavily burdened by huge regional disparities. Although, they existed in the self-government socialistic period even before the independence of the Croatian state, during the recent 20 years these disparities have widened. At the county level and NUTS 2 level in Croatia it is observed significant demographic, socio-economic and other interregional disparities. The population, economic activities and income are polarised. The developmentally depressed regions of Croatia covered around 47% of the territory, and in that area around 28% of Croatian population was settled. That is why a large number of counties in Croatia fall under the category of areas receiving state aid, either being Areas of Special State Concern, hilly-mountainous areas or the islands. The purpose of this paper is to analyse the strengths and constraints in resolving this problem that includes regional inequalities focusing on economy.